Analysis and Process Improvement of Flatness Defects of High Strength Hot Rolled Wide Strip Steel AG700L - Cao Shuwei; Yan Ning; Chen Quan (Teshugang, 2020)
The flatness defects of high strength hot rolled wide strip steel AG700L after uncoiling are analyzed in detail. The influences of strip shape and temperature distribution after finishing rolling are discussed, and the influences of the ratio of upper and lower water flow, side spray, cooling methods, edge masking on uncoiling plate and optimization measures are also analyzed. The results show that the main reason of the flatness defects after uncoiling is due to release of the compressive stress caused by the temperature drop of strip edge. The flatness defects could be effectively controlled by optimizing the ratio of upper and lower water flow to 1 ： 1.35 and the angle of side spray, increasing the pressure of side spray to 2.0 MPa, improving the type of cooling and using the edge masking.